Do environmental turbulence, dynamic capabilities, and artificial intelligence force SMEs to be innovative? - Maryam Hamad Al Dhaheri; Syed Zamberi Ahmad; Avraam Papastathopoulos (Journal of Innovation & Knowledge (JIK), 2024)
Although environmental turbulence poses significant challenges for small and medium-sized enterprises (SMEs), it also offers opportunities for them to thrive and compete. Scholars generally acknowledge the effectiveness of dynamic capabilities (DCs) and artificial intelligence (AI) applications in responding quickly to market uncertainties; however, their impact on boosting firm performance during real-time environmental turbulence requires further investigation. To address this gap, this study examined the influence of environmental turbulence on SME innovation using AI applications and DCs and how new opportunities can be leveraged to maintain a competitive advantage. This study adopted a quantitative approach, and survey data were collected from 487 managers and owners of SMEs that implemented DCs and AI during real-time environmental turbulence. The results indicate that the elements of environmental turbulence influence SMEs' implementation of both DCs and AI, acting as mediators between disruptive elements and enhancing firm performance during challenging times. The theoretical and practical implications of these findings are discussed in depth.
Keywords: 650; Environmental turbulence; Market turbulence; Competitive intensity; Dynamic capabilities; Artificial intelligence; SMEs